RETHINKING THE ESP COURSE FOR ENGINEERING STUDENTS AT THE NATIONAL SCHOOL OF APPLIED SCIENCES TO SUPPORT THE POST-COVID ENTREPRENEURIAL INITIATIVE IN MOROCCO - Dahbi, Manar (POLISSEMA – Revista de Letras do ISCAP, 2022)
Morocco adopted strong health security measures to confront early on the global outbreak of coronavirus. However, like other middle-income countries the health emergency and lockdown strategy has resulted in a substantial economic hardship and unemployment increase. To face this problem of higher unemployment rates, mainly among young graduates, Morocco has further promoted an already adopted strategy to create multiple investment opportunities to develop the “entrepreneurial spirit” among students. Higher education institutions have been called, hence, to respond to and support this post- Covid 19 initiative. In this respect, the aim of this paper is to report the results of an action research project on the integration of entrepreneurial soft skills activities in the English curriculum to help engineering students of the National School of Applied Sciences of Fes acquire the essential skills they need for a better professional integration as future entrepreneurs and initiators of innovative projects. At the end of this study, the participants had to answer a survey questionnaire on their perceptions of this teaching/ learning program. The results reveal a positive attitude of the respondents and stress the importance of incorporating learning activities in English classes that enhance soft skills. The results also emphasize some recommendations on the need for students to take part in on-site training by mentors in the workplace during their internship to have a chance to learn from genuine first-hand experiences.